Tawajjuh and Islamic Therapy: Improving Subjective Well-being - Farhan, Muhammad; Ramazana, Ramazana (Universitas Muhammadiyah Yogyakarta, 2024)
The present research is descriptive qualitative research that examines tawajjuh as one part of Sufism developed by Tarikat Naqsyabandiah from Aceh. The data in this research was obtained from interviews with people who have practised tawajjuh and students who live in Islamic educational institutions (dayah) that implement tawajjuh values and related studies in various journals, books and scientific studies. Tawajjuh is a series of spiritual activities to lead the counselee (jama'ah) to always be mindful of God through a direct relationship with a mentor face-to-face in one assembly by reciting several dhikr as a form of worship. This research aims to develop Tawajjuh as an Islamic therapeutic approach, promoting integrated and fostered subjective well-being. Based on the study, tawajjuh can increase subjective well-being in an exemplary manner. The study found a series of stages of tawajjuh as an Islamic therapy to foster positive subjective well-being.